Local government reform as state building: What the Polish case says about “decentralisation” - Levitas, Anthony (Journal of Public Governance, 2018)
Objective: Since 1990, Poland has become one of the most decentralised states in Europe. Local governments now control a third of all public expenditures. They have also delivered the goods, modernising the country’s infrastructure and restructuring its schools. This article attempts to explain why local government reform was so successful in Poland, and what it tells us about “decentralisation” elsewhere.Research Design & Methods: Historical research, practitioner experience, comparative analysis.Findings: The success of Polish local government reform was not due to “bottom up” accountability arising from either civic engagement or local taxation. Instead, “decentralisation” was largely a technocratic revolution from above. But accountability was created through an array of mezzo level institutions that trained and professionalised newly elected local elites, while also embedding them in the regulatory structure of the state and forcing them to monitor themselves.Implications / Recommendations: “Decentralisation” is less dependent on “getting the rules right” or mobilising popular engagement than it is on creating institutions that encourage public officials to learn from, and monitor, each other.Contribution: Reappraisal of what needs to be done to make “decentralisation” work. History of local government reform in Poland.